In-depth characterization of Klebsiella pneumoniae carbapenemase (KPC)-encoding plasmids points at transposon-related transmission of resistance genes - van Almsick, Vincent F.; Sobkowiak, Annika; Scherff, Natalie; Schuler, Franziska; Oehm, Johannes Benedict; Böing, Christian; Mellmann, Alexander; Schwierzeck, Vera (Frontiers in Cellular and Infection Microbiology, 2025)
Antimicrobial resistance (AMR) is a growing threat in healthcare systems, particularly in the management of infections in critically ill patients. This study highlights how to identify clusters and putative sharing of mobile genetic elements, such as transposons, in the hospital setting using long-read whole genome sequencing (lrWGS). The approach described here can be employed to investigate the transmission dynamics of KPC-3-positive Klebsiella pneumoniae at multiple levels, from the entire isolate down to individual plasmids and transposons. Here, a blaKPC-3 harboring transposon cluster was identified by using a Mash-based distance calculation for plasmids. This approach was used to investigate a local accumulation of KPC-3-positive Klebsiella pneumoniae on surgical and infectious disease wards of a tertiary care center in Germany over a time of six months. In total, seven patients were affected. Core genome multi-locus sequence typing analysis (cgMLST) identified two distinct genetic clusters: a sequence type (ST) 307 cluster (n = 5) and a ST101 cluster (n = 2). All isolates carried a blaKPC-3 carbapenemase. Further Mash distance-based plasmid analysis was not consistent with plasmid transfer due to genetic heterogeneity, but identified a transposon cluster across all isolates. Infection control evaluation of patient movements within their hospital admission supports a possible clonal transmission. Subsequent infection control measures, including point prevalence screening and enhanced contact precautions, successfully contained further transmissions. The study illustrates the value of in-depth plasmid analysis in understanding the transmission dynamics and epidemiology of AMR, particularly in hospital environments.